A bibliometric analysis of RNA methylation in diabetes mellitus and its complications from 2002 to 2022 - Zhang, Wenhua; Zhang, Shuwen; Dong, Chenlu; Guo, Shuaijie; Jia, Weiyu; Jiang, Yijia; Wang, Churan; Zhou, Mingxue; Gong, Yanbing (Frontiers in Endocrinology, 2022)
Background: RNA methylation has emerged as an active research field in diabetes mellitus (DM) and its complications, while few bibliometric analyses have been performed. We aimed to visualize the hotspots and trends using bibliometric analysis to provide a comprehensive and objective overview of the current search state in this field. Methods: The articles and reviews regarding RNA methylation in DM and its complications were from the Web of Science Core Collection. A retrospective bibliometric analysis and science mapping were performed by CiteSpace software to plot the knowledge maps and predict the hotspots and trends. Results: 375 qualified records were retrieved. The annual publications gradually increased over the past 20 years. These publications mainly came from 66 countries led by Canada and 423 institutions. Leiter LA and Sievenpiper JL were the most productive authors and Jenkins DJA ranked first in the cited authors. Diabetes care was the most co-cited journal. The most common keywords were “Type 2 diabetes” “cardiovascular disease” “diabetes mellitus” and “n 6 methyladenosine”. The extracted keywords mainly clustered in “beta-cell function” “type 2 diabetes” “diabetic nephropathy” “aging” and “n6-methyladenosine”. N6-methyladenosine (m6A) in DM and its complications were the developing areas of study. Conclusion: Researches on RNA methylation, especially m6A modification, were the current hotspots and the future trends in type 2 diabetes (T2D) and diabetic nephropathy (DN), as well as a frontier field for other complications of DM. Strengthening future cooperation and exchange between countries and institutions is strongly advisable to promote research developments in this field.